5t+8+11t+7=

Simple and best practice solution for 5t+8+11t+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+8+11t+7= equation:


Simplifying
5t + 8 + 11t + 7 = 0

Reorder the terms:
8 + 7 + 5t + 11t = 0

Combine like terms: 8 + 7 = 15
15 + 5t + 11t = 0

Combine like terms: 5t + 11t = 16t
15 + 16t = 0

Solving
15 + 16t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 16t = 0 + -15

Combine like terms: 15 + -15 = 0
0 + 16t = 0 + -15
16t = 0 + -15

Combine like terms: 0 + -15 = -15
16t = -15

Divide each side by '16'.
t = -0.9375

Simplifying
t = -0.9375

See similar equations:

| =2x+31 | | 5(x^3+x^2-4)-2(3x^3-2x^2)= | | tn=8n+8 | | .379555(489100-x)= | | 9+36x+36x^2=16 | | 5-(2x-(3(2-x)+6x)-10)+2x= | | 19(-13)1= | | 36x^2+36x+9=16 | | 1.45=11+y | | 2(3.14)(90.25)+2(3.14)(9.5)(h)=1616.786 | | 13-8(4t-6)=48 | | 68x+8x^2-17x^3=32 | | 6z-90=30 | | 6-2x=2x+2 | | (m-n+k)(m+4n-3k)= | | (5(x^4))+(40(x^2))-100=0 | | Y=8.5c | | (2x-2y)(3x+4y)(2x-y)= | | 4(2x-3)=-3(2x+2) | | 21+x=0.84 | | ln(x)+ln(x+5)+ln(x-5)=ln(4x) | | 3(-14)+12=2(-14-3)+4 | | cos(x+70)cox(x+10)=0.5 | | 9y-4=12y+5 | | 6(p-1)=19 | | 4z/10-3=-4 | | 10(m-6)=40 | | 5x+8=-5x-7x | | ln(2a)=3 | | 68=x-10 | | 15x-24-4x=33 | | 12cos(2t)=0 |

Equations solver categories